Associations between emotions, self-focused attention and self-regulation - Παναγιώτου, Γεωργία; Αγοραστός, Δημήτρης (Psychology: the Journal of the Hellenic Psychological Society, 2018)
The present study has two aims: First it summarizes current theory and research on the association between self-consciousness/self-focused attention and different aspects of emotions in both typical and clinical populations. Second, it presents some new findings which address this association. As described in the literature, in the process of achieving one’s goals the individual compares oneself with standards and regulates one’s behavior, making behavioral adjustments or changing the goal in order to minimize the difference between one’s current status and one’s goals. During this self-evaluation process, which is an inherent part of self-regulation, attention is focused on the self and can be related to either positive or negative emotions depending on the subjective evaluation regarding the likelihood of achieving one’s goals. In psychopathology this process seems to dysfunction, so that the individual is trapped in a vicious cycle of negative emotion and increased self-focused attention/selfconsciousness. Research suggests that specific emotions, or their dimensions are associated with increased self-focused attention but it remains unclear which these dimensions are and how are related to psychopathology. Τhe findings we present attempt to separate the effects of the basic affective dimensions of valence, arousal and dominance on increased self-focused attention.